2002
DOI: 10.1128/iai.70.8.4059-4067.2002
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Identification of htrA , a Streptococcus pneumoniae Gene That Is Regulated by the CiaRH Two-Component System and Contributes to Nasopharyngeal Colonization

Abstract: Nasopharyngeal carriage is the reservoir from which most disease with Streptococcus pneumoniae arises. Survival as a commensal in this environment is likely to require a set of adaptations distinct from those needed to cause disease, some of which may be mediated by two-component signal transduction systems (TCSTS). We examined the contributions of nine pneumococcal TCSTS to the process of nasopharyngeal colonization by using an infant rat model. Whereas deletions in all but one of these systems have been asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
174
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(182 citation statements)
references
References 32 publications
6
174
1
1
Order By: Relevance
“…Considering that positive feedback strongly amplifies the production of CSP once competence has begun, the reduced efficacy of HtrA in turning competence off as opposed to blocking its initiation may be the result of higher pheromone levels at the later stage. Finally, it is important to note that although HtrA expression is regulated by at least two signaling systems (10,43), changes in HtrA levels are not responsible for the modulation of competence by this protease that allows it to serve as a sensor for the accuracy of protein biosynthesis (Fig. 6, G and H) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that positive feedback strongly amplifies the production of CSP once competence has begun, the reduced efficacy of HtrA in turning competence off as opposed to blocking its initiation may be the result of higher pheromone levels at the later stage. Finally, it is important to note that although HtrA expression is regulated by at least two signaling systems (10,43), changes in HtrA levels are not responsible for the modulation of competence by this protease that allows it to serve as a sensor for the accuracy of protein biosynthesis (Fig. 6, G and H) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray-based transcription analyses showed that the entire competence regulon including the comCDE operon was turned off in the R6ciaH C306 strain, whereas loss-of-function CiaR mutants were perfectly competent under growth conditions that prevented competence development in the wild type (36,44). On the other hand, the CiaR regulon was shown to be induced during competence within the group of "delayed" competence genes, i.e., it is itself regulated indirectly by the ComDE system (41), and evidence was presented that the CiaRH system might be required for the cells to exit normally from the competent state (6).…”
mentioning
confidence: 99%
“…The CiaRH system is an important virulence factor in systemic infections in mice and contributes to colonization of the mouse lung and the nasopharynx of infant rats (34,44,48). One of the genes controlled by CiaR, the protease/chaperone HtrA, has recently been analyzed in detail and appears to be the main mediator of the virulence phenotype and competence inhibition of cia mutants (21,22,44,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized of these is ComDE, which activates the genetic competence system in response to a competence-stimulating peptide (6,7). Another system, CiaRH, also affects competence and has been shown to control a novel virulence factor, HtrA (8,9). More recently, HK͞RR04 has been linked to the control of the Mn transporter PsaA, although this regulation was apparently strainspecific (10).…”
mentioning
confidence: 99%